Evaluation of thermo-triggered drug release in intramuscular-transplanted tumors using thermosensitive polymer-modified liposomes and MRI - Kokuryo, Daisuke; Nakashima, Seiji; Ozaki, Fuminori; Yuba, Eiji; Chuang, Kai-Hsiang; Aoshima, Sadahito; Ishizaka, Yukihito; Saga, Tsuneo; Kono, Kenji; Aoki, Ichio (Nanomedicine, 2015)
Multi-modal thermo-sensitive polymer-modified liposomes (MTPLs) containing an anticancer drug, MR contrast agent, and fluorescent dye have been investigated as “theranostic” nanodevices that can be used to monitor drug delivery in cancer therapy. Here, we measured the physical characteristics of MTPLs, observed the dynamics of MTPLs in vivo, visualized heat-triggered drug release using MRI, and evaluated the treatment effects of the MTPLs with and without heating. In vitro experiments demonstrated that the MTPLs released drugs at temperatures above 41°C. In vivo MTPLs accumulated in tumor tissue, with the accumulation maximized for 4-12hours. MR signal in the tumor was significantly elevated after mild heating for 15 minutes, indicating release of the contrast agent from the MTPLs was facilitated by heat-triggering. Tumor size after treatment with MTPLs and heating was significantly smaller than those of the control groups. In conclusion, MTPLs with MRI are useful for low-invasive cancer theranostics. This team of investigators measured the physical characteristics of multi-modal thermo-sensitive polymer-modified liposomes, observed their dynamics in vivo, visualized drug release after heat-triggering using MRI, and evaluated the treatment effects of the MTPLs with and without heating, concluding that their approach may be useful in low-invasive cancer therapy. Multimodal thermo-sensitive polymer-modified liposomes (MTPLs) containing anticancer drugs, MR contrast agents, and fluorescent dyes were investigated as a theranostic nanodevice. This paper observed the MTPL accumulation in tumor, visualized thermo-triggered drug release and temperature distribution, and assessed treatment efficacy in intramuscular transplanted colon-26 tumors using in vivo MRI. Drug release from MTPL triggered by mild hyperthermia (42.5°C, for 10minutes) was visualized using MRI, and the effects of treatment in the tumor were evaluated. [Display omitted]